This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: dM dx = V + P dw dx Since P = 0, dM dx = V ⇒ M = V a x + const ⇒ 0 at x = L M = V a ( x − L ) Displacement: d 4 w dx 4 = 0 ⇒ d 3 w dx 3 = const L x y Figure by MIT OCW. But M = − D d 2 w dx 2 = 0 , dM dx = − D d 3 w dx 3 = V a d 3 w dx 3 = − V a D d 2 w dx 2 = − V a D ( x − L ) Subject to w , dw dx = 0 at x = 0 w = V a x 2 2 D ( L − x 3 ) ⇒ cubic displacement...
View
Full Document
 Fall '10
 ywn

Click to edit the document details